Sustainability of Suburban Industrial Development through Place Attachment - Liwei Lu; Dingjiang Long; Yen-Ching Chuang; Marcel Pikhart; Xiaoyan He (Civil Engineering Journal, 2022)
This research uses urban space reconstruction as the entry point, discussing the characteristics of residents’ sense of place in Lingang new town, Shanghai, based on the method of factor analysis to divide the sense of place into place attachment, place identity, and place dependence. On the whole, residents’ sense of place in Lingang new town is at a common level, and the comprehensive score of residents’ sense of place in Lingang new town is "more than half". Meanwhile, place attachment is the highest, place dependence is the lowest, and place identity is in the middle. Therefore, the sense of place mainly depends on place attachment. Using an independent T test and variance analysis to explore the characteristics of the sense of place, this paper has found that age, income level, education level, household registration, and migration patterns have significantly different influences on the three dimensions of the sense of place. There is no difference in gender and the type of occupation, whether they are working in Lingang New Town or not. The research on the sense of place in suburban industrial development zones presents a new perspective for solving the social space problems in the development zone. Finally, this research suggests improving the construction of public facilities, paying more attention to youth groups’ sense of place, and enhancing the sense of belonging to the highly educated groups and high-income groups, as well as strengthening innovation and entrepreneurship cooperation between the new town and the main city. Doi: 10.28991/CEJ-2022-08-07-014 Full Text: PDF